Delays in the Management of Retroperitoneal Sarcomas. (19th September 2010) - Seinen, Jojanneke; Almquist, Martin; Styring, Emelie; Rydholm, Anders; Nilbert, Mef
Abstract : Retroperitoneal sarcomas are rare and treatment should optimally be centralized. Despite successful centralization with 90% of the patients referred prior to surgery, delays occur, which led us to assess lead times in a population-based series. Method . Patients diagnosed with retroperitoneal sarcoma in the southern Sweden health care region 2003–2009 were eligible for the study. Data on referrals and diagnostic investigations were collected from clinical files from primary health care, local hospitals, and from the sarcoma centre. Lead times were divided into patient delays and health care delays caused by primary health care, local hospitals, or procedures at the sarcoma centre. Results . Complete data were available from 33 patients and demonstrated a median patient delay of 23 days (0–17 months) and median health care delay of 94 days (1–40 months) with delays of median 15 days at the general practitioner, 36 days at local hospitals, and 55 days at the sarcoma centre. Conclusion . Centralization per se is not sufficient for optimized and efficient management. Our findings suggest that delays can be minimized by direct referral of patients from primary health care to sarcoma centers and indicate that development of coordinated diagnostic packages could shorten delays at the sarcoma centre.